(untitled) - David R Lovett (Bristol, UK, 1994)
This book explains the properties of soap films and soap-bubbles. Then, it uses their properties to illustrate and elucidate a wide range of physical principles and scientific phenomena in a way that unifies different concepts. The book is supported with: over 100 diagrams and photographs; details of practical experiments that can be performed using simple household materials; computer programs that draw some of the more complicated figures or animate sequences of soap film configurations
Keywords: soap-bubbles - study and teaching